Application of Sustainable Development Concept as a Factor of International Competitiveness - Kolmosová, Lucia (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tato diplomová práce se zaměřuje na aplikaci koncepce udržitelného rozvoje ve firmě Volkswagen Slovakia na posílení její konkurenceschopnosti. Automobilová společnost je analyzována jako hráč v odvětví udržitelné mobility a její současná strategie je zhodnocena v zmyslu udržitelnosti. Na základě nejrelevantnějších aspektů analytické části je navržena řada doporučení, které by měli podpořit působení firmy v oblasti výroby elektrických vozidel a poskytování transportních služeb a které by měli přispět k dosažení eko-konkurenční výhody v daném odvětví.

This Master's thesis focuses on the application of the sustainable development concept in the company Volkswagen Slovakia to enhance its competitiveness. The automotive company is analysed as a player in the sustainable mobility industry and its current strategy is evaluated in sense of sustainability. Based on the most relevant aspects of the analytical part, several recommendations are suggested that should boost the firm's operations in the area of electric vehicles production and mobility service providing and which should contribute to achieving the eco-advantage in the industry.
Application of Sustainable Development Concept as a Factor of International Competitiveness
Keywords: udržitelný rozvoj; konkurenceschopnost; hodnota; udržitelná mobilita; elektrická vozidla; ekologická efektivnost; sustainable development; competitiveness; value; sustainable mobility; electric vehicles; eco-efficiency